Reaction Systems for Modeling and Validation of Biological Signaling Pathways: G1/S Checkpoint of the Cell Cycle - Akcay, Nimet Ilke; Nagy, Benedek; Tuzmen, Sukru (Budapest Tech, 2021)
Reaction Systems modeling is a compact, discrete, and qualitative modeling method for dynamic systems, including biochemical systems. In this paper, the G1/S checkpoint of the human cell cycle is modeled by Reaction Systems. This specific checkpoint is important since it plays role in tumor formation. Modeling discrete dynamic systems with Reaction Systems has many advantages over other modeling tools, i.e., the model is very small, deterministic and it is easy to use in simulations without any specific software package.
Keywords: Cell Cycle; G1/S checkpoint; Reaction Systems; Simulation